2016
DOI: 10.1371/journal.pone.0156757
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Mitogenomics: A Comparison of Approaches Applied to Caecilian Amphibian Phylogeny

Abstract: Mitochondrial genome (mitogenome) sequences are being generated with increasing speed due to the advances of next-generation sequencing (NGS) technology and associated analytical tools. However, detailed comparisons to explore the utility of alternative NGS approaches applied to the same taxa have not been undertaken. We compared a ‘traditional’ Sanger sequencing method with two NGS approaches (shotgun sequencing and non-indexed, multiplex amplicon sequencing) on four different sequencing platforms (Illumina’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…The latter two models require the input data to be non-partitioned. The CAT-GTR site mixture model implemented in Phylobayes-MPI 1.7a (Lartillot et al, 2007) allows for site-specific rates of mutation, which is considered to be a more realistic model of amino acid evolution, especially for large multi-gene alignments (Maddock et al, 2016). GHOST model is an edge-unlinked mixture model consisting of several site classes with separate sets of model parameters and edge lengths on the same tree topology, thus naturally accounting for heterotachous evolution (Crotty et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The latter two models require the input data to be non-partitioned. The CAT-GTR site mixture model implemented in Phylobayes-MPI 1.7a (Lartillot et al, 2007) allows for site-specific rates of mutation, which is considered to be a more realistic model of amino acid evolution, especially for large multi-gene alignments (Maddock et al, 2016). GHOST model is an edge-unlinked mixture model consisting of several site classes with separate sets of model parameters and edge lengths on the same tree topology, thus naturally accounting for heterotachous evolution (Crotty et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The mitogenome enrichment strategy recently proposed by Macher et al (2017b) may be highly relevant in this context. Alternatively, a more affordable strategy may consist in extending sampling in a pilot assay to identify mt genome regions with high information content, which may then be targeted by PCR using primers designed for indexed multiplex amplicon sequencing (Maddock et al, 2016;Meimberg et al, 2016). In our phylogenetic analysis, G. roeselii, G. fossarum and G. pulex form a well-supported clade, a feature also observed in other studies based on either a limited set of partial mt DNA and nuclear DNA sequences (e.g., Hou et al, 2011) or a set of 13 mt protein-coding genes (Macher et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Recently identified phylogeographic patterns within the archipelago's endemic herpetofauna have revealed a variety of geographic correlations: skinks and geckos broadly differentiate into northern (Praslin and surrounding islands) and southern (Mahé, Silhouette, and surrounding islands) groups (Rocha et al, 2010;Rocha et al, 2011;Valente et al, 2013;Rocha et al, 2016a;Rocha et al, 2016b); while for the nonsooglossid anurans, a distinct lack of variability is shown in the multi-distributed treefrog Tachycnemis seychellensis (Maddock et al, 2014), conflicting with observed structuring in Seychelles endemic caecilians (Adamson et al, 2016;Maddock et al, 2016;Maddock et al, 2017). Our mtDNA analyses appear to confirm the relationship posited by Taylor et al (2012), namely that Silhouette and Praslin populations of So.…”
Section: Biogeographic and Conservation Implicationsmentioning
confidence: 99%